KONSEP PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM: STUDI KASUS DI DI PERGURUAN MATHLA’UL ANWAR KABUPATEN KARAWANG - Firdaus, Rusydi; Saefudin Bukhori, Didin; Rosyadi, Rahmat (Turats, 2016)
Development of curriculum in Perguruan Mathla'ul Anwar aimed at Islamic values, culture and character of students who behave tasammuh (tolerant) to understand the teachings of furu?iyah in the religion. The research is descriptive by case study was conducted on the qualitative development of Islamic education curriculum in Perguruan Mathla'ul Anwar Karawang regency. The research problems are proposed: (1) how to consept a curriculum of Islamic religious education? (2) how to the contents of curriculum development of Islamic religious education?, and (3) how to the modeling of curriculum of Islamic religious education?. The study was conducted through surveys, interviews and studies with the relevant theory. The results of the study concluded that Perguruan Mathla`ul Anwar has developed a curriculum that integrated with the Islamic religious education in teaching and learning. The development of Islamic religious education curriculum is formulated into 10 subject matter set forth in the basic competencies to-Mathla'ul Anwar's include: (1) Religious Curriculum, (2) Benchmark (Minimum Standards) The Ability of Religion, (3) Local Content Curriculum , (4) Allocation of Time, (5) Management Curriculum SBC, (6) Developing Syllabus for Curriculum SBC, (7) Remedial, Enrichment And Accreditation, (8) Guidance and Counseling, (9) The Distance Education, and (10)Extracurricular.